Analisis Pola Komunikasi Kelompok Anggota Viking Persib Bandung - Fitriawati, Diny; S, Yulia Sariwaty (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
This research was conducted to find out the communication pattern of Persib Bandung supporter members who are members of the Viking Persib Club group. The method used in this research is qualitative research method, through descriptive analysis approach by borrowing Josefh A. Devito's communication pattern structure theory, research data obtained through interviews, observation, and literature study. The results showed that the communication pattern established among members of Viking Persib Club used bintang communication pattern, a pattern where all members have the same position and power to influence other members, meaning that all members can place themselves both as communicators and communicants to provide opportunities for all members to participate actively. The successful application of the bintang communication pattern fosters a sense of solidarity and loyalty that is quite high among the members of the group known as “bobotoh”. However, communication barriers are still found but more due to the individual members' understanding of the message conveyed and disturbances that affect the media when the message is delivered.